Expression of CD44, Transforming Growth Factor-β, and Matrix Metalloproteinases in Women With Pelvic Organ Prolapse - Ying, Weiwei; Hu, Yanping; Zhu, Haibin (Frontiers in Surgery, 2022)
Background: Defects in the pelvic floor connective tissue may underlie the etiology of pelvic organ prolapse (POP). We hypothesized that the expression of proteins regulating extracellular matrix turnover is altered in the uterosacral ligament of women with POP. We compared the expression of CD44, transforming growth factor (TGF)-β, and matrix metalloproteinases (MMPs) 2/9 in women with and without POP. Methods and Results: This matched case-control study included 30 postmenopausal women, with POP stage 2 and higher according to the POP quantification system, and 30 postmenopausal women without POP. Immunohistochemical analyses of the uterosacral ligament specimens obtained after hysterectomy were performed to determine CD44, TGF-β, MMP-2, and MMP-9 expression. The expression was quantified using ImageJ software, and the association between prolapse occurrence and risk factors was evaluated using Spearman’s correlation analysis. CD44 expression was significantly lower (p < 0.05), whereas MMP-2 and MMP-9 expression was higher (p < 0.0001 and p < 0.05, respectively), in the POP group than in the control group. The expression of TGF-β was similar in both groups. The occurrence of uterine prolapse was positively correlated with age, postmenopausal age, and MMP-2 and MMP-9 expression (p < 0.01) and negatively correlated with CD44 expression (p < 0.05). Conclusion: CD44, MMP-2, and MMP-9 may play critical roles in the pathogenesis of POP and may be candidate biomarkers of POP progression.